ARCHEOLOGY OF EXCLUSION: COUNTER-MAPPING SITES OF EXCLUSION AND OPPRESSION IN THE ADMINISTRATIVE STATE USING GIS - SANTIS, ESTEBAN LEONARDO (Public administration quarterly, 2018)
As public administration continues to explore geographic information systems (GIS), the field needs to take critical GIS seriously. Herein, I demonstrate that critical GIS can help public administration scholars and practitioners counter-map sites of oppression and exclusion, which has important implications for a socially just administrative state. This study begins with a theoretical discussion about the role of exclusion and oppression in the administrative state by way of Agamben’s (1998; 2004) state of exception, Kristeva’s (1982) abjection, and Quijano’s (1992; 2000) coloniality of power thesis. Thereafter, I look at exclusion and oppression in praxis, followed by a case study that examines the shooting of seventeen-year-old Trayvon Martin in Sanford, Florida, on the evening of February 26, 2012. Here, counter-maps show a stark juxtaposition of concentrated affluence and disadvantage in Sanford; which points to a series of inequalities that quite possibly empowered George Zimmerman’s decision to abject Trayvon Martin.